Creating Highlander Wherever You Are. (August 2016) - Williams, Susan; Mullett, Cathy
Highlander Research and Education Center serves as a catalyst for grassroots organizing and movement building. This article focuses on an interview with education coordinator Susan Williams who has worked at Highlander for 26 years. We discuss how others can and do create powerful popular education experiences anywhere, whether they have a dedicated space or not. In this article, we address four concerns to create a Highlander-like setting. Key deliberations include the process before, during, and after workshops or meetings in that space; values and strategizing, establishing why a space is being provided and what collective outcomes are desired from meeting in that space; cultural aspects and importance; and the challenge of a physical place. Weaving these concerns together into an anticipated outcome can then take projects and ideas forward into participants' communities of service.